Analysis of Factors That Inhibit the Economy in Pager Village, Rakumpit District - Endang Sri Suyati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
: This research aims to determine the factors inhibiting the economy in Pager Village, Rakumpit District, Palangkaraya City in terms of economic and non-economic factors. Method: The research method used in this research is qualitative research methods. In this study, the primary data sources referred to in this research include 1 village head, 1 village staff, 1 RT head, 1 RW head, 2 farmer communities, and 2 planter communities. Data collection techniques use observation, interviews, and documentation. Result and Discussions: The results of the research show that the factors inhibiting the economy in Pager Village, Rakumpit District, Palangka Raya City are economic sub-optimality, labor shortages, lack of community unity, challenges in farming and gardening, the need for better coordination and collaboration, and not an optimal use of natural resources. Apart from that, non-economic factors such as infrastructure, services, regular meetings, and public awareness are also obstacles.